Rebekah Holden: capstone - Holden, Rebekah, artist (Colorado State University. Libraries, 2016)
The artist's statement: As an artist, I have learned a lot about how I work as a designer: I love designs with bold color, I love organization, and I love using photography within graphic design. Typically when I use colors in my designs, the colors are strong, eye-catching colors. I spend a lot of time researching colors and the emotive qualities they represent before I use them in my design work. Organizing information is something that has more recently caught my attention - a style I have adapted after discovering how much I enjoy web design and user experience systems. After finishing an internship with the CSU communications office, I learned that some of my best work is produced when photography is incorporated into my designs. Photography now plays a dominant role in a lot of my design work, and it is what makes my work a little bit different than that of other designers. In my opinion, within graphic design, photography that is done well allows for the piece to become just personal enough to engage the audience.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design